Analysis of the Effectiveness of Employee Work Implementation at the Regional Secretariat of Sigi Regency - Nurivana Nurivana; Rajindra Rajindra; Haris Abd. Kadir (Universitas Muhammadiyah Palu, 2020)
The purpose of this study was to determine and analyze the effectiveness of the work implementation of employees at the Regional Secretariat of Sigi Regency according to standard operating procedures. The results of the study indicate that the quantity of work is related to work concentration, work completion, expertise and additional work time. The amount of work can be obtained from the results of the answers to the questionnaire of the state civil apparatus, which reveals that the level of work quantity can optimally complete the workload given. The quality of work at the Regional Secretariat of Sigi Regency is closely related to the effectiveness of the work produced; this is due to the level of accuracy of the state civil servants. In optimizing working time, and the greater the knowledge they have, especially theoretical ones. The Regional Secretariat of Sigi Regency is a government organization that cannot be separated from services to the community, the use of time in work is required to improve organizational governance and use of resources to complete work by established operational standards